A green-light-emitting, spontaneously blinking fluorophore based on intramolecular spirocyclization for dual-colour super-resolution imaging. Issue 1 (7th December 2017) - Uno, Shin-nosuke; Kamiya, Mako; Morozumi, Akihiko; Urano, Yasuteru
Abstract : We have developed the first green-light-emitting, spontaneously blinking fluorophore (SBF), HEtetTFER. Abstract : We have developed the first green-light-emitting, spontaneously blinking fluorophore (SBF), HEtetTFER. In combination with our near-infrared-light-emitting SBF (HMSiR), HEtetTFER allows dual-colour single-molecule localization microscopy (SMLM) in buffer solution without any additive and without photoactivation.